Australian Rotavirus Surveillance Program: Annual Report, 2024 - Thomas, Sarah; Bogdanovic-Sakran, Nada; Pavlic, Daniel; Bines, Julie; Donato, Celeste (Communicable Diseases Intelligence, 2025)
This report from the Australian Rotavirus Surveillance Program describes the circulating rotavirus genotypes identified in children and adults during the period 1 January to 31 December 2024. In 2024, we saw a continuation of a high burden of rotavirus disease in the Australian population. During this period, 2,118 faecal specimens were referred to the National Rotavirus Reference Centre (NRRC), for rotavirus G- and P-genotype analysis; of these samples, 1,880 were confirmed as rotavirus positive. This is the second highest number of samples referred to the NRRC over the past 20+ years of operation. Of the 1,880 samples confirmed rotavirus positive, 1,610 (85.6%) were identified as wildtype rotavirus; 268 (14.3%) were identified as the Rotarix vaccine-like strain; and two G1P[8] samples could not be confirmed as wildtype or vaccine-like due to inadequate sequence quality. The equine-like G3P[8] variant was the dominant genotype nationally (n = 1,297/1,610; 80.6%). Other genotypes were identified at low frequencies including G1P[8] (n = 9/1,610; 0.6%); G2P[4] (n = 34/1,610; 2.1%); G3P[8] (n = 77/1,610; 4.8%); G8P[8] (n = 46/1,610; 2.9%); G9P[4] (n = 9/1,610; 0.6%); G9P[8] (n = 6/1,610; 0.4%); and G12P[8] (n = 8/1,610; 0.5%). Genotype distribution was consistent nationally, with equine-like G3P[8] the dominant genotype in all jurisdictions. Consistent with observations in recent years, a small number of samples with unusual genotypes were identified (n = 70/1,610; 4.3%). Of these unusual genotypes, the most frequently detected was G2P[8], which accounted for 52.9% of unusual samples (n = 37/70) and 2.3% of all positive wildtype samples (n = 37/1,610). The high number of rotavirus positive samples received by the program reflected the notifications for rotavirus disease reported to the National Notifiable Disease Surveillance Service (NNDSS). Across Australia, there were 10,108 notifications recorded, the highest reported in any year since establishment of the national rotavirus notification. The ability to monitor the genotypes of rotavirus strains causing disease across ages and across jurisdictions provides important data to aid in assessing the performance of the national rotavirus vaccination program and to inform public health interventions during outbreaks. The Australian Rotavirus Surveillance Program also provides important data to monitor annual variations in genotypes circulating in the population. Understanding the diversity of genotypes in circulation, and the emergence of variants, provides important context for any changes observed in disease epidemiology in the community. The Australian Rotavirus Surveillance Program provides diagnostic laboratories with valuable feedback on laboratory data quality, by reporting incidences of wildtype, vaccine-like, and/or false positive rotavirus results.